SPINK6 inhibits human airway serine proteases and restricts influenza virus activation. Issue 1 (26th November 2021) - Wang, Dong; Li, Cun; Chiu, Man Chun; Yu, Yifei; Liu, Xiaojuan; Zhao, Xiaoyu; Huang, Jingjing; Cheng, Zhongshan; Yuan, Shuofeng; Poon, Vincent; Cai, Jian‐Piao; Chu, Hin; et al.
Abstract: SPINK6 was identified in human skin as a cellular inhibitor of serine proteases of the KLK family. Airway serine proteases are required to cleave hemagglutinin (HA) of influenza A viruses (IAVs) to initiate an infection in the human airway. We hypothesized that SPINK6 may inhibit common airway serine proteases and restrict IAV activation. We demonstrate that SPINK6 specifically suppresses the proteolytic activity of HAT and KLK5, HAT‐ and KLK5‐mediated HA cleavage, and restricts virus maturation and replication. SPINK6 constrains the activation of progeny virions and impairs viral growth; and vice versa, blocking endogenous SPINK6 enhances HA cleavage and viral growth in physiological‐relevant human airway organoids where SPINK6 is intrinsically expressed. In IAV‐infected mice, SPINK6 significantly suppresses viral growth and improves mouse survival. Notably, individuals carrying the higher SPINK6 expression allele were protected from human H7N9 infection. Collectively, SPINK6 is a novel host inhibitor of serine proteases in the human airway and restricts IAV activation. Synopsis: Serine protease inhibitor Kazal‐type 6 (SPINK6) restricts influenza A virus (IAV) extracellular maturation via inhibiting proteolytic cleavage of the influenza virus hemagglutinin (HA) by human airway trypsin‐like protease (HAT) and kallikrein 5 (KLK5). SPINK6 was identified as a novel host inhibitor of serine proteases in the human airway. SPINK6 restricts IAV activation and replication by inhibiting HA cleavage by HAT and KLK5. Endogenous SPINK6 blocks IAV maturation and viral growth in human airway organoids. SPINK6 ameliorates disease outcome in influenza virus‐infected mice. Higher SPINK6 expression allele protects individuals from human H7N9 infection. Abstract : Serine protease inhibitor Kazal‐type 6 (SPINK6) restricts influenza A virus (IAV) extracellular maturation via inhibiting proteolytic cleavage of the influenza virus hemagglutinin (HA) by human airway trypsin‐like protease (HAT) and kallikrein 5 (KLK5).